The Mechanical Properties Requirement for Polymer Composite Automotive Parts - A Review - Muhamad Fitri; S. Mahzan; Fajar Anggara (Institute for Research on Innovation and Industrial System (IRIS), 2020)
Indonesia has a large variety of natural fibers in abundance. Some of natural fibers become organic waste if not used for something needed by humans. One of the potential uses of natural fiber composite materials is to be used in automotive components. But before natural fiber composites are used in automotive components, it is necessary to examine first what are the requirements for mechanical properties or other properties required by the automotive components. Especially the automotive components which have been made from Polymers, like dash board, Car interior walls, front and rear bumper and Car body, etc. Each of these automotive components has different function and condition, and that caused different mechanical properties needed. The purpose of this study is collecting the data from the literature, related to the properties needed for these automotive components. This study was conducted by studying the literature of research journals in the last 10 years. From the research journals, data on the requirements of mechanical properties for automotive components will be collected. Furthermore, the data of mechanical properties required for automotive components can be used as a reference to determine the reliability of automotive components made from composite